“Farming with alternative pollinators” provides benefits also in large-scale fields - Bencharki, Youssef; Michez, Denis; Ihsane, Oumayma; Reverté, Sara; Aw-Hassan, Aden A.; Smaili, Moulay Chrif; Ssymank, Axel; Rasmont, Pierre; Christmann, Stefanie (Elsevier, 2024)
Insect pollinators are declining worldwide due to many challenges and several approaches have been implemented to mitigate their loss. Farming with Alternative Pollinators (FAP) uses marketable habitat enhancement plants (MHEP) that yield substantial benefits for farmers from the first year. Studies with small-scale farmers have shown that FAP sustains high diversity and abundance of flower visitors and natural enemies, resulting in significant increases in smallholders' incomes, on average 121% higher. For the first time, we analyzed this approach in large-scale fields. Trials were conducted in 16 farms in two regions of Morocco, Sidi Slimane and Ksar El-Kebir, in 2021. We used melon (Cucumis melo) as the main crop and coriander, anise and sunflower as MHEP and selected in each farm 1 ha as trial area in larger monocultures. We compared FAP and control fields regarding abundance and richness of flower visitors, natural enemies and pests as well as net income of the whole field (1 ha). Flower visitors and natural enemies were significantly more diverse and abundant in FAP fields and there were also fewer pests. Our economic results show 17% higher net income per ha in FAP fields versus control fields in the Ksar El-Kebir region, and 12% higher net income in FAP fields compared to control fields in Sidi Slimane region. Although the mean yield difference was statistically significant, the income difference was not. We suggest more FAP trials are needed in different large-scale fields systems.